The stiffness-dependent tumor cell internalization of liquid metal nanoparticles. Issue 45 (7th November 2022) - He, Jing; Pang, Wen; Gu, Bobo; Lin, Xubo; Ye, Jian
Abstract : Stiff liquid metal nanoparticles would be endocytosed faster than their soft counterparts when the active targeting between the nanoparticles and cells exists, and this tendency turns over when only passive interaction exists. Abstract : The properties of nanoparticle (NP) carriers, such as size, shape and surface state, have been proven to dramatically affect their uptake by tumor cells, thereby influencing and determining the effect of nanomedicine on tumor theranostics. However, the effect of the stiffness of NPs on their cellular internalization remains unclear, especially for circumstances involving active or passive NP targeting. In this work, we constructed eutectic gallium indium liquid metal NPs with the same particle size, shape and surface charge properties but distinct stiffness via tailoring the surface oxidation and silica coating. It has been found that the softer NPs would be endocytosed much slower than their stiffer counterparts in the presence of specific ligand–receptor interaction. Interestingly, once the interaction is eliminated, softer NPs are internalized faster than the stiffer ones. Based on experimental observations and theoretical verification, we demonstrate that this phenomenon is mainly caused by varying degrees of deformation of soft NPs induced by ligand–receptor interactions. Such a finding of the stiffness effect of NPs implies great potential for fundamental biomedical applications, such as the rational design of nanomedicines.